Integration of geoscience data to delineate quality of the Asmari reservoir, Iranian part of the Persian Gulf basin. (June 2023) - Abdolahi, Aziz; Bahrehvar, Mohammad; Chehrazi, Ali; Kadkhodaie, Ali; Wood, David A.
Abstract: The Hendijan Field is an asymmetric structure located in the northwestern Persian Gulf and consists of several oil and gas-bearing intervals. Oligocene to Miocene successions in the field host large volumes of hydrocarbons. The Asmari Formation comprises the mixed siliciclastic and carbonate members formed in a shallow marine carbonate ramp depositional environment. The siliciclastic part displays the best reservoir quality within the Asmari Formation. Through petrophysical, sedimentological, and geophysical analysis, this study divides the Asmari Formation into six, third-order depositional sequences. By doing so, it clarifies the relationships between depositional sequences and reservoir characteristics, particularly porosity and water saturation. Detailed petrographical analysis, core description, well log analysis, and seismic interpretation distinguish eight microfacies, two petrofacies, and six third-order sequences within the Asmari Formation. 3D reservoir-property models are developed that incorporate elements of the sequence stratigraphical framework. Within the six identified sequences, high reservoir quality zones are associated with AS-4 and AS-5, which comprise mostly grain-supported lithologies associated with shoal facies. The supratidal, intertidal, and lagoonal facies of AS-2, which are often associated with the occurrence of anhydrite and mud-supported fabrics, reflect lower reservoir quality. Hydraulic flow units (HFU) are delineated to assist in characterizing reservoir heterogeneity and porosity/permeability prediction. Five HFU were identified by applying the flow-zone-indicator method to evaluate reservoir quality. Both the transgressive system tract (TST) of AS-2 and early TST plus late highstand system tract (HST) of AS-6 contain elements of HFU-A. The most productive units of AS-4 and AS-5 belong to HFU-E. Highlights: Porosity and water saturation are the most important reservoir properties. Sequence stratigraphy controls distribution of reservoirs characteristic. Hydraulic flow units used to link the petrophysical properties to reservoir quality.